Characterization of carotenoid profiles and presence of functional markers in sub-tropical maize (Zea mays L.) inbred lines - Amoah, P.; Adetimirin, V.; Anokye, B.; Ilesanmi, O.J.; Unachukwu, N.; Aporva, E.I. (2025)
Biofortification provides a sustainable, pragmatic strategy to address the lack of vitamin A and the associated health complications. The objectives of the study encompassed the quantification of the carotenoid content of 147 maize inbred lines, the identification of variable regions within the ZEP1 gene, the correlation of these observed variances in the presence of this gene with carotenoid content, and the identification of lines harbouring the favourable alleles of the crtRB1 gene. The observed correlations among the carotenoids synthesised by distinct branches of the biosynthetic process were both significant and positive. Utilising gel-based genotyping, 24 lines with contrasting carotenoid profiles were selected, evaluated and sequenced. Analysis of the variation in the sequence classified these lines based on their similarities to give 8 allele groups. The findings highlight that inbred lines both group 1 and group 8 exhibited significant associations with the carotenoid content of the lines. Specifically, ZEP1_7852, a discernible variation belonging to group 8, was found to be significantly associated with zeaxanthin content and total carotenoid content. Furthermore, 25 lines were found to have provitamin A content above 15 μg/g, harbouring the favourable alleles of the crtRB1 gene using KASP SNP zm0016. These lines can serve as parents for source populations and hybrids, leading to the further enhancement of provitamin A in maize.